Assessment of the Role of C3(H2O) in the Alternative Pathway - Fromell, Karin; Adler, Anna; Åman, Amanda; Manivel, Vivek Anand; Huang, Shan; Dührkop, Claudia; Sandholm, Kerstin; Ekdahl, Kristina N.; Nilsson, Bo (Frontiers in Immunology, 2020)
In this study we investigate the hydrolysis of C3 to C3(H2O) and its ability to initiate activation via the alternative pathway (AP) of the complement system. The internal thioester bond within C3 is hydrolyzed by water in plasma because of its inherent lability. This results in the formation of non-proteolytically activated C3(H2O) which is believed have C3b-like properties and be able to form an active initial fluid phase C3 convertase together with Factor B (FB). The generation of C3(H2O) occurs at a low but constant rate in blood, but the formation can be greatly accelerated by the interaction with various surfaces or nucleophilic and chaotropic agents. In order to more specifically elucidate the relevance of the C3(H2O) for AP activation, formation was induced in solution by repeated freeze/thawing, methylamine or KCSN treatment and named C3(x) where the x can be any of the reactive nucleophilic or chaotropic agents. Isolation and characterization of C3(x) showed that it exists in several forms with varying attributes, where some have more C3b-like properties and can be cleaved by Factor I in the presence of Factor H. However, in common for all these variants is that they are less active partners in initial formation of the AP convertase compared with the corresponding activity of C3b. These observations support the idea that formation of C3(x) in the fluid phase is not a strong initiator of the AP. It is rather likely that the AP mainly acts as an amplification mechanism of complement activation that is triggered by deposition of target-bound C3b molecules generated by classical/lectin pathway (CP/LP) convertases.